1995
DOI: 10.1002/ijc.2910630504
|View full text |Cite
|
Sign up to set email alerts
|

gelatinase A/TIMP‐2 imbalance in lymph‐node‐positive breast carcinomas, as measured by RT‐PCR

Abstract: Over-production of gelatinase A (MMP-2) or under-production of its inhibitor (TIMP-2) may result in the matrix degradation crucial for metastasis, and early evaluation of their expression in primary tumor would offer important prognostic informations. RT-PCR amplicons of MMP-2 and TIMP-2 mRNA from tissue biopsies of 13 breast carcinomas and one fibrocystic mastopathy were quantitated. In comparison with their normal-tissue counterparts, their expression trends were not uniform: in some cases MMP-2 increased in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 14 publications
3
38
0
1
Order By: Relevance
“…The observed increase in MMP-2 expression observed in tumor samples is consistent with previous studies of breast (41,42), colon (43)(44)(45)(46)(47), stomach (48,49), lung (50 -53), rectal (43,54), and kidney cancer (55)(56)(57). Whereas a strong association of increased MMP-3 has been found in breast cancer (41, 58 -61), the increased expression levels observed in other tumor types are not as well supported by published literature.…”
Section: Sibling Expression and Tumor Progressionsupporting
confidence: 92%
“…The observed increase in MMP-2 expression observed in tumor samples is consistent with previous studies of breast (41,42), colon (43)(44)(45)(46)(47), stomach (48,49), lung (50 -53), rectal (43,54), and kidney cancer (55)(56)(57). Whereas a strong association of increased MMP-3 has been found in breast cancer (41, 58 -61), the increased expression levels observed in other tumor types are not as well supported by published literature.…”
Section: Sibling Expression and Tumor Progressionsupporting
confidence: 92%
“…In the human body, the expression of MMP-2 and TIMP-2 overlaps in the various different tissues and proteolysis occurs as a result of an imbalance between MMP-2 and TIMP-2 activity. 9,10 MMP-2 has been implicated in a number of situations such as development, morphogenesis and tumor progression, where remodeling of the tissue architecture and alteration of ECM turnover occur. [11][12][13][14] Several studies have reported that MMP-2 is up-regulated in the course of different malignancies and is involved in tumor metastasis.…”
mentioning
confidence: 99%
“…It is well known that in urothelial cancer patients the mean MMP-2/TIMP-2 ratio in patients with recurrence is significantly higher than that in patients without recurrence and the disease-free survival of patients with high MMP-2/TIMP-2 ratio is extremely poor compared with that of patients with lower ratios (Gohji et al, 1996). It was demonstrated also that evaluation of MMP-2: TIMP-2 mRNA balance may constitute an early prognostic indicator of human cancer (Onisto et al, 1995). Evidently, the elevation of the balance of MMP-2 and TIMP-2 in endometriotic tissue results in increase of invasive potential of ectopic endometrium.…”
Section: Changes Of the Invasiveness Of Endometrium In Endometriosismentioning
confidence: 99%